Factors influencing consumers' preferences towards meat and meat products with traceability systems in Malaysia - Mohd Nawi, Nolila (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2018)
Majority consumers around the world have become increasingly concern and aware about their health and food safety. Recent food crisis and foodborne illness incidents showed the needs to assure the authenticity and traceability of foods in the market especially meat and meat products. These scandals have led to negative effect and perception to consumers, food companies and both supply and demand chain. Hence, the food industry needs an excellent and reliable traceability system to ensure that consumers are persistently well protected from unconscious consumption of unsafe foods. Therefore, traceability systems can support the claims by making it verifiable. However, the awareness among Malaysian consumers is still lacking due to the inadequate exposure towards concept and the importance of traceability systems particularly in meat and meat products. The aim of this study is to determine factors influencing consumers’ preferences towards traceability systems of meat and meat products in Malaysia. Primary data were collected using structured questionnaire via face to face interview with 503 respondents in Klang Valley, Malaysia. Data collected were analyzed using descriptive and factor analysis. The findings of descriptive analysis showed that most of the consumers preferred using traceability systems and aware of its importance when buying meat and meat products. Meanwhile, the factor analysis results discovered six factors that influenced consumers’ preferences towards meat and meat products with traceability systems namely Halal certificate, transparency, quality, confidence, food safety and knowledge. Therefore, implementation of traceability systems could raise standards of food safety throughout the meat production supply chain. Furthermore, the society will become more confident and they can benefit from the quality of purchase and consumption. The findings from this study are also able to contribute to the body of knowledge to the producers or marketers towards food safety issues and foodborne illness that recently happened in Malaysia.